The Implementation of Explicit Instruction with Hyponymy Game in Teaching Vocabulary - Jenifer Niske Sangkek; Rizqi Claudia Wardani.H (English Education Program Universitas Pendidikan Muhammadiyah Sorong, 2025)
The objective of this research was to determine whether the implementation of explicit instruction combined with the hyponymy game has an impact on students’ vocabulary at the eighth grade of SMPN I Aitinyo. This study applied a pre-experimental quantitative research design using a one-group pretest–posttest design. The sample consisted of 20 eighth-grade students in one class. Data were collected using a vocabulary test consisting of 20 items (15 multiple choice and 5 matching items). The data were analyzed using SPSS 31. The findings showed that the P-value (0.001) was lower than 0.05, meaning that H₀ was rejected and Hₐ was accepted. This indicates that there was a significant impact of teaching vocabulary using explicit instruction combined with the hyponymy game between the pretest and posttest. The mean score increased from 49.25 in the pretest to 71.5 in the posttest. The results imply that explicit instruction supports clear word understanding, while the hyponymy game makes learning more engaging. This study suggests that creative approaches can enhance vocabulary teaching. However, this research has several limitations: it involved only one class without a comparison group, focused only on noun vocabulary, and observed students only during classroom activities without examining learning outside the classroom.